Planejamento tributário e legalidade: a teoria do propósito negocial no positivismo contemporâneo - Rodrigues, Pedro Jacob (2020)
This study examines the application of business purpose theory to tax planning from the perspective of Contemporary Positivism, specially under the perspective of Wilfrid Waluchow’s inclusive positivism. Initially it seeks to present an overview of Legal Positivism, from its origin to what can be called Contemporary Positivism. Next, it examines the Principle of Legality, as it is the most relevant to be considered with this theme. Having built a solid theoretical fundament, the study turns to the analysis of Tax Planning, differentiating it from Tax Evasion and Tax Elusion. At this point, it is also important to differentiate vices and defects in acts and legal business, indicating the possibility, or not, of its application for purposes of invalidation of tax planning. Among these figures, Simulation is highlighted, due to the possibility of its application to invalidate tax planning. From this, it starts to study the business purpose doctrine, from its origin in the United States of America to its incorporation in Brazil. Then it becomes possible to examine the practical cases in which the mentioned doctrine was applied by the judges of the Board of Tax Appeals (CARF). For this purpose, the operations selected were the so called “Constitute and Dissolve”, “Segregation of Activities”, “Downstream Merger”, and “Amortization of Goodwill through the use of Vehicle Company” were selected. After examining each of these types of Tax Planning, it is possible to evaluate how the doctrine of business purpose is applied in the Brazilian federal administrative jurisprudence from the perspective of Wilfrid Waluchow’s Inclusive Positivism